2018
DOI: 10.1002/adsc.201801018
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Induced Aerobic Oxidative −H Arylation of Glycine Derivatives

Abstract: A direct aerobic oxidative dehydrogenative coupling reaction of glycine derivatives with electron-rich arenes has been accomplished via the synergistic combination of organic-dye mediated photoredox catalysis and Lewis acid catalysis. This process exhibits good tolerance of functional groups and provides rapid synthesis of arylglycine derivatives at room temperature under an air atmosphere. Moreover, this protocol could be performed on a 10 mmol scale, without obvious reduction of the yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 92 publications
0
9
0
1
Order By: Relevance
“…[72] In 2018, Li et al reported the visible-light-induced CDC reaction of glycine derivatives with phenols and unexpectedly discovered trace amount of 1,3-benzoxazine during the reaction (Scheme 14a). [73] Inspired by this observation, in 2020, they proposed and reported the capture of another equivalent of imine intermediate by glycine ester under the synergistic catalysis of visible light and Lewis acid, thus providing a new intermolecular CDC strategy for the synthesis of 1,3-benzoxazines (Scheme 14b). [74] They proposed a plausible mechanism for this new CDC strategy: glycine ester 54 was oxidized by Ru(II)* to produce radical cation 57 via SET, then 57 lost protons to produce iminium ion 58.…”
Section: Combining Lewis Acid Catalysis With Photoredox Catalysismentioning
confidence: 99%
“…[72] In 2018, Li et al reported the visible-light-induced CDC reaction of glycine derivatives with phenols and unexpectedly discovered trace amount of 1,3-benzoxazine during the reaction (Scheme 14a). [73] Inspired by this observation, in 2020, they proposed and reported the capture of another equivalent of imine intermediate by glycine ester under the synergistic catalysis of visible light and Lewis acid, thus providing a new intermolecular CDC strategy for the synthesis of 1,3-benzoxazines (Scheme 14b). [74] They proposed a plausible mechanism for this new CDC strategy: glycine ester 54 was oxidized by Ru(II)* to produce radical cation 57 via SET, then 57 lost protons to produce iminium ion 58.…”
Section: Combining Lewis Acid Catalysis With Photoredox Catalysismentioning
confidence: 99%
“…2012 年, 包 明等 [71] 发现间氯过氧苯甲酸(mCPBA)可以直接氧化 均具有良好的耐受性, 偶联反应发生在酚羟基的邻位, 具有极高的区域选择性(Schemes 25b, 26), 此外, 大位 阻的 1,3,5-三甲氧基苯也可以与甘氨酸酯发生 CDC 反 应. 此后, 李瀛等 [73] 以有机染料 Rhodamine 6G (Rh 6G) [74] . 唑类作为一类具有多种药理活性的杂芳烃化合物, 具有一定的抗肿瘤、抗病毒及抗菌等 [75] 作用, 是修饰各 类活性氨基酸的优秀官能化试剂.…”
Section: C(sp 3 )-C(sp )偶联反应unclassified
“…In 2018, another relay photoredox reactionw as developed by the group of Zhang (Scheme 29). [50] This transformation implies photoredox oxidation of ag lycine ester 68.T hiso rganocatalyzed reactioni ns itu generates ar eactive imine, further coordinating to the iron-based Lewis acid. The decreased electron density on this electrophile facilitates the addition of naphthol generating the expected product 70.A pplication of an achiral iron complexl eads to the formation of ar acemic product.…”
Section: A Achiral and Racemic Reactionsmentioning
confidence: 99%
“…In 2018, another relay photoredox reaction was developed by the group of Zhang (Scheme 29). [50] This transformation implies photoredox oxidation of a glycine ester 68 . This organocatalyzed reaction in situ generates a reactive imine, further coordinating to the iron‐based Lewis acid.…”
Section: Organo‐/iron Catalysismentioning
confidence: 99%